The P/NiFe doped NiMoO4 micro-pillars arrays for highly active and durable hydrogen/oxygen evolution reaction towards overall water splitting. (20th September 2019) - Zhuang, Shuxian; Tong, Siyuan; Wang, Hailiang; Xiong, Hailang; Gong, Yi; Tang, Yang; Liu, Jia; Chen, Yongmei; Wan, Pingyu
Abstract: Water splitting is an efficient strategy to produce purity hydrogen and convert intermittent electricity from renewable wind and solar sources. In this work, dense NiMoO4 micro-pillars arrays (MPAs) were in-situ grown on nickel foam (NF) through facile hydrothermal method, then the NiMoO4 /NF were converted into NiMoO4 –P/NF and NiFe/NiMoO4 /NF via phosphating and electrodeposition method, respectively. The NiMoO4 –P/NF electrode required small overpotentials of 34 mV@10 mA cm −2 and 130 mV@100 mA cm −2 for hydrogen evolution reaction (HER). The NiFe/NiMoO4 /NF electrode exhibited excellent oxygen evolution reaction (OER) activity with overpotentials of 210 mV@10 mA cm −2 and 300 mV@100 mA cm −2 . The overall water splitting using the anode-cathode couple of NiFe/NiMoO4 /NF||NiMoO4 –P/NF only consumes low voltages of 1.47 V@10 mA cm −2 for 100 h and 1.66 V@100 mA cm −2 for 50 h in 1 M KOH. The electronic modification and the well-designed hierarchical structure contribute the high energy-efficient and stabile overall water splitting. Graphical abstract: NiMoO4 –P/NF and NiFe/NiMoO4 /NF were fabricated on the same NiMoO4 MPAs substrate through heteroatoms doping by simple phosphating and hierarchical nanostructure engineering by electrodeposition, respectively. Benefiting from the electronic and hierarchical nanostructure modification, the prepared NiMoO4 –P/NF and NiFe/NiMoO4 /NF display low overpotential, small Rct, small Tafel slope and great stability towards HER and OER, respectively. The water splitting device using NiFe/NiMoO4 /NF as anode and NiMoO4 –P/NF as cathode only requires a cell voltages of 1.47 V@10 mA cm −2 for 100 h and 1.66 V@100 mA cm −2 for 50 h without decay during the durability tests.Image 1 Highlights: Ultralow cell voltage of 1.47 V was achieved at 10 mA cm −2 for more than 100 h. Heteroatoms doping and nanostructure engineering of NiMoO4 micro-pillar arrays. NiMoO4 –P/NF with modified electronic structure shows excellent HER performance. NiFe/NiMoO4 /NF with hierarchical structure shows superior OER performance.